2011
DOI: 10.3389/fnana.2011.00059
|View full text |Cite
|
Sign up to set email alerts
|

Basal Ganglia Disorders Associated with Imbalances in the Striatal Striosome and Matrix Compartments

Abstract: The striatum is composed principally of GABAergic, medium spiny striatal projection neurons (MSNs) that can be categorized based on their gene expression, electrophysiological profiles, and input–output circuits. Major subdivisions of MSN populations include (1) those in ventromedial and dorsolateral striatal regions, (2) those giving rise to the direct and indirect pathways, and (3) those that lie in the striosome and matrix compartments. The first two classificatory schemes have enabled advances in understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
470
0
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 383 publications
(510 citation statements)
references
References 286 publications
(438 reference statements)
16
470
0
11
Order By: Relevance
“…Afferent connections present in the matrix, especially in the lateral part of the dorsal striatum, are related to sensomotor areas of the cerebral cortex. Matrix located more medially and striosomes have predominant associative-and limbic-related connections, respectively [11]. Similarly to data from previous successful demonstration of systemic proteasome inhibitors' effect on damage of nigrostriatal connections [32,33,38,51], we observed a loss of dopaminergic terminals within the striatum.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Afferent connections present in the matrix, especially in the lateral part of the dorsal striatum, are related to sensomotor areas of the cerebral cortex. Matrix located more medially and striosomes have predominant associative-and limbic-related connections, respectively [11]. Similarly to data from previous successful demonstration of systemic proteasome inhibitors' effect on damage of nigrostriatal connections [32,33,38,51], we observed a loss of dopaminergic terminals within the striatum.…”
Section: Discussionsupporting
confidence: 71%
“…The striatum is responsible for integrating in coming information from all areas of the cerebral cortex and creating motor patterns based on past knowledge (procedural memory) and on the recent environment and desires [11]. The striosome/matrix cytoarchitectonic structures of the striatum play a crucial role in its functional organization.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Starr et al (2011), using probabilistic tractography, found that areas of the putamen activated by painful stimuli have extensive anatomical connectivity with numerous cortical and subcortical regions involved in emotion and memory (amygdala and hippocampus), nociceptive processing (insula, ACC), and higher-order cognition (premotor cortex, BA8). Thus, the basal ganglia might potentially play a key role in modulating pain, via its anatomical connections with limbic, sensorimotor, and cognitive "loops" (Alexander and Crutcher, 1990;Crittenden and Graybiel, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Striatal output neurons segregate into patch and matrix compartments, which are defined on the basis of different input-output connections and specific neurochemical markers (Crittenden and Graybiel, 2011). The striatal patch compartment, also referred to as striosomes, is enriched in -opioid receptor (MOR), whereas the extrastriosomal matrix compartment is composed of neurons containing the calbindin-D28k (Calb-D28k).…”
Section: D-amph Increases Rps6 Phosphorylation In Striatonigral Msns mentioning
confidence: 99%